Preservatives used in Pharmaceuticals and impact on Health (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2024)
For several decades pharmacist have been aware of the need to protect their products againstmicrobial contamination but it is only during the last one or perhaps two decades the seriousthought of has been applied to the science of preservation. Preservatives are commonly used asadditives in pharmaceutical products, food and cosmetics. Some of the liquid preparations aresusceptible to microbial contamination because of the nature of ingredients present in it. Suchpreparations are protected by preservatives which avoids degradation and alternation of theproduct. A preservative is a natural or synthetic chemical added to various products which helpsto prevent microbial decomposition. Present article deals with the study of ideal properties,classification, and mechanism of action, pharmaceuticals applications and its impacts on healthof various preservatives used in pharmaceuticals.